Improved floatability of low-rank coal through surface modification by hydrothermal pretreatment. (10th February 2020) - Yang, Zili; Guo, Fangyu; Xia, Yangchao; Xing, Yaowen; Gui, Xiahui
Abstract: Low-rank coal (LRC) contains a developed pore structure and rich oxygen-containing functional groups (OCFG). Therefore, it cannot easily be upgraded using flotation technology. In this study, simple and effective hydrothermal pretreatment (HP) was performed to reduce the porosity and increase the hydrophobicity of LRC surface. LRC characteristics, such as coal composition, surface morphology, pore structure, and surface functional groups were analyzed before and after HP. The results showed that, after HP, the coals exhibited lower amounts of moisture and volatile matter, but substantially greater amounts of fixed carbon than raw coal. Pore structure analysis indicated the collapse and closure of many pores on the coal surface, indicating in low porosity in the pretreated coal. In addition, X-ray photoelectron spectroscopy revealed more hydrophobic functional groups and less OCFG on the coal surface. It is, therefore, HP resulted in excellent flotation recovery, with increased recovery of 70.7% combustible material. Highlights: Hydrophilic OCFG decomposed with the increasing HP temperature and time. The porosity decreased with the increasing HP temperature and time. Floatability of LRC increased with the increasing HP temperature and time. 70.70% combustible matter recovery was obtained after HP for LRC-300-90. Surface modification method of HP benefits LRC clean and efficient separation.